Potensi Diri dalam Islamic Edupreneurship: Takwa, Kreativitas dan Inovasi - Indah, Henik Nur (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research aims to explore self-potential in the context of Islamic Edupreneurship that integrates the values of piety, creativity, and innovation. Islamic Edupreneurship focuses on the development of entrepreneurship in line with Islamic law, integrating religious values with modern business principles. Piety acts as a moral foundation that encourages individuals to act honestly and ethically, while creativity and innovation are key in creating products and services that benefit society. This research uses a qualitative approach with a literature study, reviewing various relevant literature to understand how self-potential can be developed within the framework of Islamic Edupreneurship. The results show that holistic self-potential development, covering spiritual, emotional, and intellectual aspects, is the key to creating excellent and highly competitive individuals in a competitive business world.